1992
DOI: 10.1300/j013v18n04_05
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Exploitation in Advertising Health and Wellness Products

Abstract: This paper examines the way women are portrayed by the media in photographs advertising health and wellness products. Data were collected from five different health and fitness magazines. For purposes of this study, only advertisements in which women appeared were used in the analysis (N = 191). Findings suggest that a high percent of advertisements: (1) place women in submissive positions to men; (2) place women in unnatural poses; (3) emphasize dismemberment of body parts; (4) focus on sexuality rather than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 5 publications
0
20
0
Order By: Relevance
“…In addition, a more precise measure of degradation could be developed rather than relying on the time-consuming method of ratings made by another sample. Cowan and Dunn (1994) determined themes in pornography that people found degrading, and others have looked at themes of subjugation of women in advertising (e.g., Rudman & Hagawara, 1992), so their methods might prove helpful in developing a rating system for degrading pictures. Finally, it is important to link the use of degrading images with behavior that is more likely to approximate rape than a rape supportive attitude scale such as a measure of self-report of past SA (e.g., Koss & Gidycz, 1985) or self-report of future likelihood to rape (e.g., Malamuth, 1981).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a more precise measure of degradation could be developed rather than relying on the time-consuming method of ratings made by another sample. Cowan and Dunn (1994) determined themes in pornography that people found degrading, and others have looked at themes of subjugation of women in advertising (e.g., Rudman & Hagawara, 1992), so their methods might prove helpful in developing a rating system for degrading pictures. Finally, it is important to link the use of degrading images with behavior that is more likely to approximate rape than a rape supportive attitude scale such as a measure of self-report of past SA (e.g., Koss & Gidycz, 1985) or self-report of future likelihood to rape (e.g., Malamuth, 1981).…”
Section: Discussionmentioning
confidence: 99%
“…First is the visual objectification of women's bodies. For example, content analytic work has demonstrated that women' bodies are more emphasized, through close-ups, dismemberment, and high body display, than men's bodies (Archer et al 1983;Goffman 1979;Rudman and Hagiwara 1992). Relevant to the second class of objectifying media is the media's tendency to emphasize women's bodies through textual framing.…”
Section: Objectification Theorymentioning
confidence: 99%
“…In the visual category, several content analyses have shown that the media tend to focus on isolated body parts, such as a bare stomach, buttocks, cleavage, or a bare chest, in the absence of a focus on the rest of the person (Rudman & Hagiwara, 1992;Sommers-Flanagan, Sommers-Flanagan, & Davis, 1993). Advertising in both women's magazines (Frith, Shaw, & Cheng, 2005;Rudman & Hagiwara, 1992) and on television (Reichert, Lambiase, Carstarphen, & Zavoina, 1999), as well as music videos (Sommers-Flanagan et al, 1993), use these visual shortcuts extensively. For example, Reichert et al found that 29% of their sample of award-winning television commercials contained a seductively dressed model.…”
Section: Objectification Theorymentioning
confidence: 99%